A C5a-Immunoglobulin complex in chronic lymphocytic leukemia patients is associated with decreased complement activity - Michelis, Regina; Tadmor, Tamar; Barhoum, Masad; Shehadeh, Mona; Shvidel, Lev; Aviv, Ariel; Stemer, Galia; Dally, Najib; Rahimi-Levene, Naomi; Yuklea, Mona; Braester, Andrei (PLOS ONE, 2019)
Chronic lymphocytic leukemia (CLL) is the most common adult leukemia in the Western world. The therapeutic approach to CLL includes chemotherapeutic regimens and immunotherapy. Complement-mediated cytotoxicity, which is one of the mechanisms activated by the therapeutic monoclonal antibodies, depends on the availability and activity of the complement (C) system. The aim was to study the structure of circulating C components and evaluate the importance of C5 structural integrity for C activity in CLL patients. Blood samples were collected from 40 naïve CLL patients and 15 normal controls (NC). The Western blot analysis showed abnormal C5 pattern in some CLL patients, while patterns of C3 and C4 were similar in all subjects. Levels of the C activation markers sC5b-9 and C5a were quantified before and after activation via the classical (CP) and alternative (AP) pathways. In patients with abnormal C5, basal levels of sC5b-9 and C5a were increased while activities of the CP and of the CP C5-convertase, the immediate C5-upstream complex, were decreased compared to NC and to patients with normal C5. The data indicate a link between CP activation and apparent C5 alterations in CLL. This provides a potential prognostic tool that may personalize therapy by identifying a sub-group of CLL patients who display an abnormal C5 pattern, high basal levels of sC5b-9 and C5a, and impaired CP activity, and are likely to be less responsive to immunotherapy due to compromised CP activity.